Non-blue Haslea species (Bacillariophyceae: Naviculaceae) in the benthic marine flora of Guam (Mariana Islands, Western Pacific Ocean). Issue 2 (2nd April 2020) - Lobban, Christopher S.; Perez, Claire O.; Ashworth, Matt P.
Abstract : In recent years the taxonomy of Haslea has been in flux. We describe several Haslea taxa from Guam, including four new species, in light of these recent findings. Four delicate, fusiform Haslea species are described from a variety of benthic habitats on coral reefs. These species, H. fusiformis comb. nov. and H. alexanderi, H. apoloniae and H. guahanensis spp. nov. are distinguished by stria density, foramen ('areola') shape, and cell size from each other and from similar taxa. A key to all these taxa is provided. In addition, an arcuate species is described as Haslea arculata sp. nov. The presence of a bilayered wall is shown for all these taxa. We compare the morphology of specimens reported as H. howeana from Guam with Navicula tsukamotoi, recently described from Okinawa, and with ' Navicula cf. howeana ' from Puerto Rico. We provide the first account of the complex cingulum of N. tsukamotoi . We conclude that our specimens match N. tsukamotoi and that H. howeana should be returned to Navicula, but we leave open the question of conspecificity.